College campus smoking policies and programs and students' smoking behaviors - Cohen Lee; Bacchi Donna; Xu K Tom; Borders Tyrone F; SoRelle-Miner Danielle (BMC, 2005)
Abstract Background Although tobacco use in the United States has declined over the past 20 years, cigarette use among college students remains high. Additional research is thus needed to determine how university tobacco control policies and preventive education programs affect college students' smoking behaviors. Methods Approximately 13,000 undergraduate students at 12 universities or colleges in the state of Texas completed a web-based survey. College smoking policies were obtained from a survey of college administrators and from college websites. Logistic regression analyses were conducted to estimate the effects of individual smoking policies and programs on the odds of cigarette smoking. Results Of the individual programs, only having a preventive education program on campus was associated with lower odds of smoking. The existence of smoking cessation programs and designated smoking areas were associated with higher odds of smoking. Policies governing the sale and distribution of cigarettes were insignificantly associated with smoking. Conclusion Rather than focusing on policies restricting cigarette sales and use, college administrators should consider implementing or expanding tobacco prevention and education programs to further reduce student smoking rates.